Conductive heterogeneous blend composites of PP/PA12 filled with ionic liquids treated-CNT. (April 2019) - Lopes Pereira, Elaine C.; Soares, Bluma G.; Silva, Adriana A.; Farias da Silva, Juliana M.; Barra, Guilherme M.O.; Livi, Sebastien
Abstract: Multi-walled carbon nanotube (CNT) was non-covalently functionalized with alkyl phosphonium-ionic liquids bearing phosphinate (IL-TMP) and bistriflimide (IL-TFSI) as the counter-anions in proportions of 1:1 and 1:5 by weight) to obtain black pastes that were incorporated in polypropylene (PP)/polyamide12 (PA12) (80:20 wt. %) blend by melt mixing. All composites were prepared with 1 phr of CNT. The effect of the ILs on the AC electrical conductivity, rheological measurements, thermal properties and dielectric properties of the PP/PA12 composites was evaluated. Also, the morphology of the composites was studied by transmission electron microscopy (TEM) and scanning electron microscopy (SEM). The presence of IL resulted in an increase of the electrical conductivity and the best performance was achieved by using IL-TFSI where a proportion of CNT/IL-TFSI = 1:1 was enough to promote an improvement of this property by three orders of magnitude. This system also presented improved complex viscosity and increased storage modulus, obtained by dynamic-mechanical analysis (DMA). CNT has a tendency to be located at the PA12 phase as indicated by TEM, but the presence of IL-TFSI also contributes for the localization of CNT in both phases, which may be the reason for the outstanding electrical performance. The CNT/IL interactions were also investigated by Raman spectroscopy. Highlights: -Dual role of Ionic Liquids as dispersant aids of CNT as well as compatibilizing agents of PP/PA12 blends. Improved conductivity of the composites by using CNT non-covalently functionalized with IL. Higher melt viscosity of composites containing CNT/IL reinforcing filler system. Development of new conductive polymer composites with good electrical conductivity and thermo-mechanical properties.